2022
DOI: 10.1021/acsomega.2c02217
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment in CO2 Absorption by 2-Methyl Piperazine-Activated Tertiary Amines, Physical Solvents, and Ionic Liquid Systems

Abstract: One of the ever-demanding research fields is the development of new solvents with better properties for mitigation of CO 2 compared to existing solvents. This work reports the measurement and modeling of CO 2 solubility in newly proposed aqueous solvent blends of 2-methyl piperazine with N -methyldiethanolamine (MDEA), sulfolane (TMSO 2 ), and 1-butyl-3-methyl-imidazolium acetate ([bmim] [Ac]). The operating temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Research has indicated that the effectiveness of the solvent mixture for CO 2 extraction can be enhanced by combining MDEA with activators. 2-Amino-2-methyl-1-propanol (AMP), piperazine (PZ), amino ethyl ethanol amine (AEEA), and diethanol amine (DEA) are the common activators used to increase the reaction kinetics and absorption capacity of aqueous amine solvents [28,29]. In industry, PZ blended with MDEA has been commonly employed as the standard solvent for purifying natural gas.…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that the effectiveness of the solvent mixture for CO 2 extraction can be enhanced by combining MDEA with activators. 2-Amino-2-methyl-1-propanol (AMP), piperazine (PZ), amino ethyl ethanol amine (AEEA), and diethanol amine (DEA) are the common activators used to increase the reaction kinetics and absorption capacity of aqueous amine solvents [28,29]. In industry, PZ blended with MDEA has been commonly employed as the standard solvent for purifying natural gas.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ionic liquids have attracted much attention due to their specific properties, such as undetectable vapor pressure, easy to separate from the reaction system, and environmentally friendly. Hence, ionic liquids have been used in many fields, especially in catalysis; it was proved that a large number of reactions could be catalyzed by ionic liquids, such as esterification, carbonylation, cycloaddition, and alkylation reaction. …”
Section: Introductionmentioning
confidence: 99%